CHALLENGES AND INNOVATIONS IN SCIENTIFIC AND TECHNICAL TRANSLATION: TERMINOLOGICAL COMPLEXITIES AND ‘FALSE FRIENDS’ - Radetska, Svitlana (The Modern Higher Education Review, 2024)
This article explores the dynamic changes in scientific and technical terminology at the start of the 21st century, driven by global advancements in science, technology, and international cooperation. The focus is on the complexities faced by translators in identifying, characterizing, and translating new terms, especially those complicated by ‘false friends of translators.’ The study analyses the processes of terminology formation, the polysemy of terms, and the challenges posed by synonymy and the absence of equivalent terms in the target language. The research employs methods such as literature review, comparative analysis, and lexical-semantic analysis to understand the formation and usage of terminology in English and Ukrainian. It also highlights the influence of English on global terminological vocabulary, particularly in economic and computer sciences. The article emphasizes the importance of accurate translation in scientific communication and suggests strategies for improving translation practices through standardization, training, and collaboration. This research aims to contribute to the ongoing development and standardization of Ukrainian scientific and technical terminology, ensuring clarity, precision, and effective communication in specialized fields.